2010
DOI: 10.1177/1545109710368151
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Rapid HIV Antibody Tests in 5 African Countries

Abstract: The sensitivity and specificity of three rapid HIV antibody tests were assessed at five clinical trial sites in Africa and one site in the United States using a minimum of 100 HIV antibody positive samples and 100 HIV antibody negative samples at each site. The overall sensitivity and specificity for the OraSure OraQuick, Abbott Determine, and Trinity Unigold tests were 99.3%, 99.8% and 98.5%, respectively, and 99.3%, 99.4%, and 99.5%, respectively. There were no instances at any site in which false negative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 4 publications
1
35
0
1
Order By: Relevance
“…There are conflicting reports in the literature regarding false-positive rates for the rapid test. Some studies report a sensitivity of > 99% and specificity of > 99%, whereas other groups suggest higher rates of false-positive rapid tests (16,(25)(26)(27)(28). Proposed theories for this discordance in the literature may be multifactorial.…”
Section: Discussionmentioning
confidence: 80%
“…There are conflicting reports in the literature regarding false-positive rates for the rapid test. Some studies report a sensitivity of > 99% and specificity of > 99%, whereas other groups suggest higher rates of false-positive rapid tests (16,(25)(26)(27)(28). Proposed theories for this discordance in the literature may be multifactorial.…”
Section: Discussionmentioning
confidence: 80%
“…On one side we find very simple dipstick-based immunochromatographic (ICT) assays for self-testing, such as the rapid HIV test kits that provide a result in less than 30 min from an oral swab [3]. On the other side we find relatively sophisticated and expensive instruments that are used in hospitals for molecular diagnosis that also require trained personnel for their use.…”
Section: Introductionmentioning
confidence: 98%
“…Validation studies previously conducted in five African countries showed that the Abbott Determine kit has a sensitivity of 99.80% and a specificity of 99.40%, and the Trinity Uni-Gold kit has a sensitivity of 98.50% and a specificity of 99.50%. These tests require minimal infrastructure and provide results quickly [40]. 2.…”
Section: Dependent Variablementioning
confidence: 99%